Electrophysiological Mechanisms and Therapeutic Potential of Calcium Channels in Atrial Fibrillation - Zuyuan Huang; Cheng Luo; Zimin Wu; Baoshi Zheng (Reviews in Cardiovascular Medicine)
Atrial fibrillation (AF) is a prevalent and complex arrhythmia for which the pathogenesis involves various electrophysiological factors, notably the regulation of calcium channels. This article aimed to investigate the specific roles and molecular mechanisms of the L-type and T-type calcium channels, ryanodine receptors (RyRs), inositol 1,4,5-triphosphate receptors (IP3Rs), calcium release-activated calcium (CRAC) channels, and transient receptor potential (TRP) channels in the pathogenesis and persistence of AF. In addition, this article reviews recent advances in calcium channel-targeted drugs from experimental and clinical studies, offering new insights into the relationship between calcium channel regulation and AF pathology. These findings suggest promising directions for further research into the mechanisms of AF and the development of targeted therapeutic strategies.